Plasma membrane proteome analysis identifies a role of barley membrane steroid binding protein in root architecture response to salinity. (15th March 2018) - Witzel, Katja; Matros, Andrea; Møller, Anders L.B.; Ramireddy, Eswarayya; Finnie, Christine; Peukert, Manuela; Rutten, Twan; Herzog, Andreas; Kunze, Gotthard; Melzer, Michael; Kaspar‐Schoenefeld, Stephanie; Schmülling, Thomas; et al.
Abstract: Although the physiological consequences of plant growth under saline conditions have been well described, understanding the core mechanisms conferring plant salt adaptation has only started. We target the root plasma membrane proteomes of two barley varieties, cvs. Steptoe and Morex, with contrasting salinity tolerance. In total, 588 plasma membrane proteins were identified by mass spectrometry, of which 182 were either cultivar or salinity stress responsive. Three candidate proteins with increased abundance in the tolerant cv. Morex were involved either in sterol binding (a GTPase‐activating protein for the adenosine diphosphate ribosylation factor [ZIGA2], and a membrane steroid binding protein [MSBP]) or in phospholipid synthesis (phosphoethanolamine methyltransferase [PEAMT]). Overexpression of barley MSBP conferred salinity tolerance to yeast cells, whereas the knock‐out of the heterologous AtMSBP1 increased salt sensitivity in Arabidopsis . Atmsbp1 plants showed a reduced number of lateral roots under salinity, and root‐tip‐specific expression of barley MSBP in Atmsbp1 complemented this phenotype. In barley, an increased abundance of MSBP correlates with reduced root length and lateral root formation as well as increased levels of auxin under salinity being stronger in the tolerant cv. Morex. Hence, we concluded the involvement of MSBP in phytohormone‐directed adaptation of root architecture in response to salinity. Abstract : Salt tolerance is an important agronomic trait, and there is a high interest in unravelling mechanisms leading to improved plant performance on saline soils. In a subcellular proteomics approach, we targeted the root plasma membranes from two barley cultivars with contrasting response to the salt stress treatment. Three candidate proteins with increased abundance in the salt‐tolerant cultivar were identified and further analysed. Among those, a membrane steroid binding protein, MSBP, conferred salinity tolerance to yeast cells, whereas knock‐out of the heterologous AtMSBP1 increased salt sensitivity in Arabidopsis . Concomitant phytohormone profiling indicated an involvement of MSBP in phytohormone‐directed adaptation of root architecture in response to salinity.